STATE AND MUNICIPAL PROGRAMS TO SUPPORT STAFF OF INSOLVENT PUBLIC TRANSPORT COMPANIES - Ivanovna Danilina, Elena; Ivanovna Malikova, Iana; Vladimirovich Gorelov, Dmitry (Revista Inclusiones, 2019)
The public transport is a means of ensuring territorial interconnections. Along with other industries, public transport is the key to the efficient development of all areas of settlements, as well as an indicator of the population’s life quality.The study aims at analyzing the possibilities and prospects of using state and municipal programs to support staff of insolvent public transport companies.In the article, the relevance of studying the problems of supporting staff of insolvent public transport companies has been specified. The efficient instruments and means of state support for the unoccupied population have been analyzed. Based on the expert survey, the components of state and municipal SIC (staff of insolvent companies) support programs have been introduced, and the terms and conditions for the efficiency of these programs have been determined.